(untitled) (Research, Society and Development, 2021)
The Anacardium occidentale L. belongs to the family Anacardiaceae, which has approximately 76 genera and 6000 species of pan-tropical distribution. Popularly known as cashew tree is a plant native to the Brazilian Northeast, having as edible parts the cashew nuts and the cashew nut, much found in the coastal sedimentary trays. In Brazil it occurs very frequently in the states of Piauí, Ceará, Pernambuco and Bahia. The objective of the present study was to carry out a scientific and technological prospection of the A. occidentale plant focused on hypoglycemic and antidiabetic activities of the plant. In the scientific prospection the articles published in the period 1951 - November/2020 were searched in the databases Pubmed, ScienceDirect, Scielo and LILACS using the following descriptors: A. occidentale, hypoglycemiant agents, diabetes mellitus and their correspondents in Portuguese: A. occidentale, hypoglycemic agents and diabetes mellitus. In the technological prospection, the patent applications filed in four databases: INPI, EPO, USPTO and WIPO using as descriptor only A. occidentale. The various articles and patents found report several pharmacological activities, among which the hypoglycemic effect demonstrated by 6 articles and 3 patents on this plant stands out. Therefore, A. occidentale has a potential hypoglycemic and antidiabetic effect to be better explored.